2021
DOI: 10.3389/fendo.2021.594001
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effects of Double-Stranded RNAs Corresponding to Multiple Vitellogenesis-Inhibiting Hormone Subtype I Peptides in Subadult Female Whiteleg Shrimp, Litopenaeus vannamei

Abstract: Vitellogenesis-inhibiting hormone (VIH) negatively regulates reproduction in shrimp and other decapod crustaceans. In order to assess the effects of transcriptional silencing by multiple VIH subtype I sinus gland peptides (SGPs) on ovarian maturation in female whiteleg shrimp, Litopenaeus vannamei, we synthesized five dsRNAs targeting Liv-SGP-A, −B, −C, −F, and −G and injected them into subadults. The following treatments were employed: sgpG-dsRNA (targeting Liv-SGP-G), sgpC-dsRNA (targeting Liv-SGP-C), and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…The seedlings of A. thaliana germinated for two weeks were used as test plants, divided into two groups: one group was treated with the mixture of ds RDR1 , ds RDR2 and ds RDR6 in equal proportions to knock down the functional RdRP genes, and the other was treated with the same dose of ds EGFP ct as control, and thus developed two plant lines with and without their RdRP genes being knocked down. Previous studies and our preliminary assays all indicated that dsRNA mixture was powerful to silence various RdRP genes in organisms 60,61 . However, too many gradients in the mixture could reduce the dose for individual genes.…”
Section: Methodsmentioning
confidence: 67%
See 1 more Smart Citation
“…The seedlings of A. thaliana germinated for two weeks were used as test plants, divided into two groups: one group was treated with the mixture of ds RDR1 , ds RDR2 and ds RDR6 in equal proportions to knock down the functional RdRP genes, and the other was treated with the same dose of ds EGFP ct as control, and thus developed two plant lines with and without their RdRP genes being knocked down. Previous studies and our preliminary assays all indicated that dsRNA mixture was powerful to silence various RdRP genes in organisms 60,61 . However, too many gradients in the mixture could reduce the dose for individual genes.…”
Section: Methodsmentioning
confidence: 67%
“…Previous studies and our preliminary assays all indicated that dsRNA mixture was powerful to silence various RdRP genes in organisms. 60,61 However, too many gradients in the mixture could reduce the dose for individual genes. Thus, in this study we did not use a mixture containing six different dsRNA to simultaneously silence another three RdRP genes without activity known in A. thaliana.…”
Section: Methods For Detecting Dsrna Contentmentioning
confidence: 99%
“…In some cultured crustaceans, reproductive dysfunction may be overcome by eyestalk ablation, which stimulates maturation, but it is associated with a high mortality rate (Gianasi, 2017;Jin et al, 2021;Asmat-Ullah et al, 2023;Jia et al, 2023). The use of dsRNA-VIH and reproductionassociated neurohormones has shown promise as a replacement for eyestalk ablation, and is highly effective in enhancing reproductive performance in several crustaceans (Cohen et al, 2021;Kang et al, 2021;Duangprom et al, 2022). In this study, we initially confirmed the role of dsRNA-VIH in the female crab S. olivacea, and showed that combinatorial administration of dsRNA-VIH, 5-HT, and GnRH, may provide the most efficient approach for manipulating reproductive maturation in captive broodstock.…”
Section: Discussionmentioning
confidence: 99%